MODIFIKASI KNALPOT MESIN DIESEL UNTUK MENGURANGI EMISI GAS BUANG DAN KEBISINGAN DI RUANGAN PABRIK PENGGILINGAN PADI - Riandi Ramlan; Dani Mardiyana (Universitas Nusa Putra, 2022)
The placement of the Type R175 diesel engine in the rice mill factory in Kebonpedes caused two problems, namely exhaust gas emissions that filled the factory room and noise levels that exceeded NAB which could cause health hazards to workers, so exhaust modifications were needed to be able to emit exhaust gases into outside the factory and also reduce engine noise that exceeds the NAB. The exhaust modification stage starts from modification design, application of exhaust modification results to diesel engines, and testing of exhaust emissions and noise levels in the factory. The exhaust emission test results before modification were CO 0.07%, CO2 3.13%, O2 14.81%, and HC 22.33 ppm and the maximum noise value before modification was 115 dB. The results of gas emission tests inside the factory after modification are CO 0.00% , CO2 0.00%, O2 20.98% , and HC 0 ppm, while the maximum noise value is 84 dB. This exhaust modification has succeeded in eliminating exhaust emissions in the factory room and reducing noise levels by 31 dB in the rice mill plant.